Factors influencing the use of public dental services: An application of the Theory of Planned Behaviour - Luzzi, Liana (BioMed Central, 2008)
BACKGROUND: There is limited evidence of the influence of psychosocial factors and health beliefs on public dental patient's patterns of service use in Australia. The research aims were to examine associations between dental attitudes and beliefs of public dental service users and dental visiting intention and behaviour using the Theory of Planned Behaviour. METHODS: 517 randomly selected adult public dental patients completed a questionnaire assessing dental attitudes and beliefs which was matched with electronic records for past and future dental service use. A questionnaire measured intentions, attitudes, subjective norms and perceptions of behavioural control and self-efficacy in relation to visiting public dentists. A measure of dental attendance at public dental clinics was obtained retrospectively (over 3 1/2 years) and prospectively (over a one year period following the return of the questionnaire) by accessing electronic patient clinical records. RESULTS: Participants had positive attitudes, subjective norms and self-efficacy beliefs towards dental visiting but perceived a lack of control over visiting the dentist. Attitudes, subjective norms, self-efficacy and perceived control were significant predictors of intention (P < 0.05). Intentions, self-efficacy and past dental attendance were significant predictors of actual dental attendance (P < 0.05). CONCLUSION: Public dental patients held favourable attitudes and beliefs but perceived a lack of control towards dental visiting. Reducing structural barriers may therefore improve access to public dental services.